Matrizes: conceitos, aplicações e o programa Geogebra - Emídio, Israel Gomes (2015)
The content of Matrices is commonly taught mechanically in high school with emphasis only on theory and monotonous calculations that discourage the teaching-learning process. But we know that, more and more, classroom dynamics require that the content taught provoke and, at the same time, satisfy the students? curiosity. The good thing is that the content of matrices gives us these possibilities. When well taught, and using appropriate tools, the content becomes more attractive and is learned more easily. Thus, the objective of this research was to show that it is possible to explore well the content of matrices through applied examples, combined with the use of the GeoGebra program. For this, we carried out a bibliographical and field research, through a case study in a public institution of primary and secondary education in the municipality of Juazeiro do Norte, Ceará. In practical terms, the research was accomplished through questionnaires applied in three tenth grade math classes, including their teachers, at the observed institution. Using the results obtained by the application of the questionnaire, it was identified that teachers and students do not know the application of the GeoGebra Software in teaching and learning the content of matrices.